Zambian Secondary School Biology Teachers' Profiles of Planned Topic-specific Pedagogical Content Knowledge for Teaching Respiration. Issue 1 (2nd January 2022) - Mapulanga, Thumah; Nshogoza, Gilbert; Yaw, Ameyaw
Abstract : Teachers' pedagogical content knowledge (PCK) has the potential to influence lesson planning, teaching and students' academic performance in science. Since PCK is embodied in lesson planning (as planned PCK), this study employed the multiple-case design to describe in-depth the biology teachers' profiles of planned topic-specific PCK (plTSPCK) for teaching respiration. While the target population comprised all biology teachers in Chipata district of Zambia, data were collected from nine teachers drawn from six secondary schools. The study used face-to-face lesson planning interviews which were audio-recorded and transcribed verbatim. Mavhunga and Rollnick's model of TSPCK was adopted as the analytical framework. After analysing each interview transcript, the teachers' integration of plTSPCK components was summarised into plTSPCK maps. The findings reveal that (a) the integration of the plTSPCK components in the teachers' profiles was idiosyncratic; (b) the components conceptual teaching strategies, curricular saliency and students' prior knowledge were central to the integration of plTSPCK; and (c) representations and what makes the topic easy/difficult were the least integrated components. The study recommends enhancing teachers' PCK through teacher professional development activities such as lesson studies using the TSPCK framework as an analysis tool for the lesson plans and the observed lesson to demonstrate the planned and enacted PCK respectively.